The oral and lower airway microbiota and coronary heart disease in COPD patients and controls - Christina Due Svendsen; Rune Nielsen; Terje H. Larsen; Karel K. J. Kuiper; Tomas M. Eagan (PLoS ONE, 2026)
Background Chronic obstructive pulmonary disease (COPD) and coronary heart disease (CHD) are major causes of morbidity and mortality, with shared risk factors and often co-occurring. This study investigated the association between both the oral and lower airway microbiome and CHD in healthy controls and COPD patients. Methods 228 participants from the MicroCOPD study (101 controls and 127 COPD patients) underwent coronary CT angiography to assess calcium score (CaSc) and coronary stenosis. Oral wash (OW) and bronchoalveolar lavage (BAL) samples were collected. Microbial DNA was analyzed using 16S rRNA gene sequencing with the Illumina MiSeq platform. Microbiome composition and diversity were analysed using established pipelines in Quantitative Insights into Microbial Ecology 2 (QIIME 2) and R. Results Alpha diversity (Shannon index) differed significantly between COPD patients and controls in OW (p < 0.01), but not BAL. No statistically significant alpha (Shannon or Faith’s PD) diversity differences were found between CHD and non-CHD groups. Beta diversity analysis (Bray-Curtis dissimilarity) revealed no significant differences in microbial composition between CHD and non-CHD groups, both for COPD patients and controls (p > 0.05). Firmicutes dominated across all subgroups, followed by Bacteroidetes and Actinobacteria . Several taxa were found to be differentially abundant between CHD and non-CHD groups but comprised less than 1% of all taxa. Conclusion The microbiome differed between COPD patients and controls, but we could not find evidence that either the oral or lower airway microbiome differed between those with and without coronary heart disease.